Reframing (Dis)Ordered Bodies: Understanding Agonias via the Habitus - Vieira Dias, Lisa (Atlantis, 2012)
The expression of agonias among Portuguese populations is an embodied experience of emotions and/or illness that defies Western medical categorization. Within Portuguese communities agonias has multiple meanings. This paper proposes that the embodiment of agonias can be understood via the habitus where the body is a meaning (re)producing social agent.